Synergistic Pd-La Catalysts on ATO for Clean Conversion of Methane into Methanol and Electricity - Paulo Victor. R. Gomes; Dolores R. R. Lazar; Gabriel Silvestrin; Victoria Amatheus Maia; Rodrigo Fernando B. de Souza; Almir Oliveira Neto (Reactions)
This study investigates the electrochemical conversion of methane to methanol using fuel-cell-type reactors with palladium- and lanthanum-based catalysts supported on antimony-doped tin oxide (ATO). The combination of these elements demonstrated promising characteristics for selective methanol production. Transmission electron microscopy (TEM) analysis revealed the impact of lanthanum addition on palladium nanoparticles, influencing size distribution and clusters. Polarization curves and power density plots highlighted the Pd50La50/ATO catalyst, indicating an optimal palladium/lanthanum ratio for methanol optimization. FTIR analysis confirmed the presence of methanol in the reaction products, while the methanol production rate showcased the superior performance of the Pd50La50/ATO catalyst compared to other compositions. The synergistic effects between lanthanum’s water activation capability and the carbophilic nature of PdO emerged as crucial factors for the catalyst’s success.